2017
DOI: 10.18632/oncotarget.14456
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke induced urocystic epithelial mesenchymal transition via MAPK pathways

Abstract: Cigarette smoke has been shown to be a major risk factor for bladder cancer. Epithelial-mesenchymal transition (EMT) is a crucial process in cancer development. The role of MAPK pathways in regulating cigarette smoke-triggered urocystic EMT remains to be elucidated. Human normal urothelial cells and BALB/c mice were used as in vitro and in vivo cigarette smoke exposure models. Exposure of human normal urothelial cells to cigarette smoke induced morphological change, enhanced migratory and invasive capacities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
4
23
0
Order By: Relevance
“…Regarding the mechanisms of WPS on the initiation of EMT and therefore cell invasion in human breast cancer cells, we assumed that the main mechanism behind these events could be Erk1/Erk2 signaling pathways, since it has been reported that tobacco smoking can provoke EMT via Erk1/Erk2 pathways [ 19 , 21 ]. Thus, Erk1/Erk2 activation was assessed in MCF7 and BT20 cell lines exposed to WPS in comparison with their matched control cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the mechanisms of WPS on the initiation of EMT and therefore cell invasion in human breast cancer cells, we assumed that the main mechanism behind these events could be Erk1/Erk2 signaling pathways, since it has been reported that tobacco smoking can provoke EMT via Erk1/Erk2 pathways [ 19 , 21 ]. Thus, Erk1/Erk2 activation was assessed in MCF7 and BT20 cell lines exposed to WPS in comparison with their matched control cells.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, recent investigations have clearly showed that both active and passive smokers have a higher risk of breast cancer development and mortality related to this disease compared to non-smokers [ 16 18 ]. On the other hand, it has been pointed out that cigarette smoking enhances cell invasion and metastatic development of different types of cancer by the initiation of epithelial–mesenchymal transition (EMT) [ 19 21 ], which is the hallmark of cancer progression [ 22 ]. Thus, it is evident that tobacco smoking can play an important role in the development and progression of several human carcinomas including breast.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that TS is strongly associated with the occurrence and development of bladder cancer. 3 , 4 It is reported that TS is the most important single risk factor for bladder cancer with 40–60% causally related. 4 Smokers have an estimated fourfold higher risk of bladder cancer than nonsmokers.…”
mentioning
confidence: 99%
“…3 , 4 It is reported that TS is the most important single risk factor for bladder cancer with 40–60% causally related. 4 Smokers have an estimated fourfold higher risk of bladder cancer than nonsmokers. 5 Accumulating evidence suggested that epithelial–mesenchymal transition (EMT) and the acquisition of cancer stem cells (CSCs) properties is an important underlying mechanisms for initiation, invasion and metastasis of cancer.…”
mentioning
confidence: 99%
“…Furthermore, we found that the p38 MAPK inhibitor SB203580 selectively suppressed CS/CSE-induced Thr-phosphorylation of Nur77, suggesting that p38 MAPK is likely the kinase responsible for this post-translational modification. CS activates the MAPK pathway that regulates activities of several transcription factors in multiple cell types [38][39][40][41]. Nur77 contains PEST (proline, glutamic acid, serine, and Thr) sequences [42], phosphorylation of which leads to rapid degradation of PEST-containing proteins [43].…”
Section: Discussionmentioning
confidence: 99%